Physics mathematization from a teaching perspective: secondary school teachers’ perceptions - Azzouzi, Abdelwahab El; Kouchou, Ihsane; Elachqar, Abdelrhani; Kaddari, Fatiha (Institute of Advanced Engineering and Science, 2025)
The courses of physics and mathematics are usually related. So, it is essential to transfer mathematical knowledge and skills to understand and solve a situation in physics. The main objective of this research is to identify teachers’ perceptions of physics mathematization. To highlight our objective, we used an analysis of textbooks and scientific literature to support a questionnaire for 141 physics teachers in the region of Fez, Meknes, Morocco. The teachers emphasized that to understand or solve problematic situations in physics it is important to go through mathematics. Still, the majority of them do not have clear ideas on how to do it. However, in the absence of a unified method, the teachers suggest some work techniques with their students whose contents are purely mathematized to overcome the difficulty of physics mathematization. This research is primarily related to curriculum development, teacher training, and the need to foster a deeper understanding of the relationship between mathematics and physics in the Moroccan educational system.